Adaptive discrete-time identification of continuous-time systems using adjusted integration - Kowalczuk, Zdzisław (Zielona Góra: Uniwersytet Zielonogórski)
A new approach to the design of on-line discrete-time systems of identification of continuous-time systems is presented. The problem concerns digital signal processing suitable for generation of the regression vector in discrete-time recursive estimation of continuous-time process parameters based on a mixed, discrete-continuous regression model.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka